Creation of the Iqra Colossal Dance at the Opening Ceremony of the National MTQ in Banjarbaru City - Proboyasti, Brusheila Devi Proboyasti (Universitas Negeri Semarang, 2024)
This research aims to explain the creation process, the history of the colossal dance “Iqra” in Banjarbaru City, South Kalimantan, and the function when creating the colossal dance. The method used in this research is qualitative. These methods focus on the location of Banjarbaru from early March to mid-June. Primary data are from direct interviews with choreographers, dancers, and head of education services. The analysis results show that this dance has a historical background in religion that can increase faith in God Almighty and has functions that range from art to Islamic. The dance creation process starts from the exploration stage, namely the stage of searching for forms of various movements. The second is improvisation, the stage of practicing the various obtained movements. In addition, the next stage is composition, the entire series carried out by the choreographers in creating the dance work “Iqra”.